2020
DOI: 10.1017/s0950268820001570
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol and environmental surface monitoring for SARS-CoV-2 RNA in a designated hospital for severe COVID-19 patients

Abstract: There is limited information concerning the viral load of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in aerosols deposited on environmental surfaces and the effectiveness of infection prevention and control procedures on eliminating SARS-CoV-2 contamination in hospital settings. We examined the concentration of SARS-CoV-2 in aerosol samples and on environmental surfaces in a hospital designated for treating severe COVID-19 patients. Aerosol samples were collected by a microbial air sampler, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 23 publications
2
93
4
Order By: Relevance
“…Of the 24 included studies, all were cross-sectional observational studies. Ten studies (41.7%) were from China, [9][10][11]15,[18][19][20]22,25,29 and the remaining were from the United States (4 [16.7%]), 12,13,26,30 Hong Kong (2 [8.3%]), 14,21 Korea (2 [8.3%]), 24,27 Singapore (2 [8.3%]), 3,16 Iran (2 [8.3%]), 8,28 the United Kingdom (1 [4.2%]), 19 and Italy (1 [4.2%]). 23 Of all included articles and studies, 20…”
Section: Characteristics Of Included Articles and Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 24 included studies, all were cross-sectional observational studies. Ten studies (41.7%) were from China, [9][10][11]15,[18][19][20]22,25,29 and the remaining were from the United States (4 [16.7%]), 12,13,26,30 Hong Kong (2 [8.3%]), 14,21 Korea (2 [8.3%]), 24,27 Singapore (2 [8.3%]), 3,16 Iran (2 [8.3%]), 8,28 the United Kingdom (1 [4.2%]), 19 and Italy (1 [4.2%]). 23 Of all included articles and studies, 20…”
Section: Characteristics Of Included Articles and Studiesmentioning
confidence: 99%
“…(83.3%) 3,[8][9][10][11][14][15][16][17][20][21][22][23][24][25][26][27][28][29][30] were published in peer-reviewed journals, and 4 (16.7%) 12,13,17,18 were posted on preprint servers.…”
Section: Characteristics Of Included Articles and Studiesmentioning
confidence: 99%
“…For COVID-19 pneumonia patients, researchers have detected the pathogen in their ward environment, especially the toilet environment ( Ong et al, 2020 ). A study reported that SARS-CoV-2 was found in mask swabs ( Li et al, 2020b ) and the air ( Guo et al, 2020 ). Viruses were widely distributed on floors, computer mouses, trash cans, and sickbed handrails and were detected in air ≈4 m from patients ( Guo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…After further screening, and supplementary searching of articles published or posted between 1 January 2020 and 21 July 2020, we identified an additional article and a total of 17 articles were included in the review (Figure 1). [3,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]…”
Section: Search Resultsmentioning
confidence: 99%